Security and Privacy for Big Data, Cloud Computing and Applications - Ren, Wei; Wang, Lizhe, 1974-; Choo, Kim-Kwang Raymond; Xhafa, Fatos (Computing series ;, 2019)
The following topics are dealt with: Big Data; data privacy; security of data; cloud computing; telecommunication security; cryptography; authorisation; Internet; social networking (online); and mobile radio.